2016
DOI: 10.3168/jds.2016-11118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a haplotype associated with cholesterol deficiency and increased juvenile mortality in Holstein cattle

Abstract: Over the last decades, several genetic disorders have been discovered in cattle. However, the genetic background of disorders in calves is less reported. Recently, German cattle farmers reported on calves from specific matings with chronic diarrhea and retarded growth of unknown etiology. Affected calves did not respond to any medical treatment and died within the first months of life. These calves were underdeveloped in weight and showed progressive and severe emaciation despite of normal feed intake. Hallmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 45 publications
3
41
0
Order By: Relevance
“…So far, the defect is clinically identifiable only in the homozygote form: Kipp et al . () reported nine cases homozygous for the disease‐associated haplotype, and Duff et al . (), Mock et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the defect is clinically identifiable only in the homozygote form: Kipp et al . () reported nine cases homozygous for the disease‐associated haplotype, and Duff et al . (), Mock et al .…”
mentioning
confidence: 99%
“…Recently, numerous calves showing retarded growth and intermittent diarrhea, accompanied by pronounced hypocholesterolemia and low triglyceride concentrations, were observed in the global Holstein population (Kipp et al . ; Mock et al . ; Schütz et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Calves show severe hypocholesterolemia and die soon after birth due to diarrhea (89). Kipp et al (89) identified a region of chromosome 11 associated with this condition on chromosome 11.…”
Section: Cholesterol Deficiency In Cattlementioning
confidence: 99%
“…Calves show severe hypocholesterolemia and die soon after birth due to diarrhea (89). Kipp et al (89) identified a region of chromosome 11 associated with this condition on chromosome 11. The analysis of the pedigree of calves, known to have died from this condition, where traced to a predominant Canadian Holstein bull (Maughlin Storm).…”
Section: Cholesterol Deficiency In Cattlementioning
confidence: 99%